Placebo and nocebo effects are defined by opposite opioid and dopaminergic responses - Scott, David J; Stohler, Christian S; Egnatuk, Christine M; Wang, Heng; Koeppe, Robert A; Zubieta, Jon-Kar (Archives of general psychiatry, 2008)
Placebo and nocebo effects, the therapeutic and adverse effects, respectively, of inert substances or sham procedures, represent serious confounds in the evaluation of therapeutic interventions. They are also an example of cognitive processes, particularly expectations, capable of influencing physiology. To examine the contribution of 2 different neurotransmitters, the endogenous opioid and the dopaminergic (DA) systems, to the development of placebo and nocebo effects. Using a within-subject design, subjects twice underwent a 20-minute standardized pain challenge, in the absence and presence of a placebo with expected analgesic properties. Studies were conducted in a university hospital setting. Twenty healthy men and women aged 20 to 30 years recruited by advertisement. Activation of DA and opioid neurotransmission by a pain stressor with and without placebo (changes in the binding potential of carbon 11 [11C]-labeled raclopride and [11C] carfentanil with positron emission tomography) and ratings of pain, affective state, and anticipation and perception of analgesia. Placebo-induced activation of opioid neurotransmission was detected in the anterior cingulate, orbitofrontal and insular cortices, nucleus accumbens, amygdala, and periaqueductal gray matter. Dopaminergic activation was observed in the ventral basal ganglia, including the nucleus accumbens. Regional DA and opioid activity were associated with the anticipated and subjectively perceived effectiveness of the placebo and reductions in continuous pain ratings. High placebo responses were associated with greater DA and opioid activity in the nucleus accumbens. Nocebo responses were associated with a deactivation of DA and opioid release. Nucleus accumbens DA release accounted for 25% of the variance in placebo analgesic effects. Placebo and nocebo effects are associated with opposite responses of DA and endogenous opioid neurotransmission in a distributed network of regions. The brain areas involved in these phenomena form part of the circuit typically implicated in reward responses and motivated behavior.